2005
DOI: 10.1097/01.sap.0000184012.63970.c3
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Large Nasal Septal Perforations Using Facial Artery Musculomucosal (FAMM) Flap

Abstract: In summary, the advantages of the FAMM flap closure technique were (1) no visible external scar, with minimal donor site morbidity; (2) successful closure of large septal defects (>2 cm) with vascularized tissue in a single stage; and (3) resolution of patient symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…This perforation was cylindrical in shape, with a diameter of 5, 10 or 15 mm for a small, medium or large perforation, respectively. Our 15 mm diameter 'large' perforation was smaller than the 20 mm diameter perforation defined as a large perforation by Heller et al 3 This was because a 20 mm perforation was found to be too large for the relatively smaller Asian nose used in the present model and simulation.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…This perforation was cylindrical in shape, with a diameter of 5, 10 or 15 mm for a small, medium or large perforation, respectively. Our 15 mm diameter 'large' perforation was smaller than the 20 mm diameter perforation defined as a large perforation by Heller et al 3 This was because a 20 mm perforation was found to be too large for the relatively smaller Asian nose used in the present model and simulation.…”
Section: Methodsmentioning
confidence: 86%
“…larger than 2 cm in diameter). 3 Numerous clinical case studies have described the surgical treatments for this condition. 1 -6 However, relatively few experimental or computer-based studies have assessed the effects of septal perforation on nasal airflow and patency.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been advocated depending on the size and site of the perforation, including external rhinoplasty 6 ; alarotomy 7 ; and endonasal, 1 sublabial, 8,9 midfacial degloving, and endoscopic procedures 10,11 Surgical procedures include enlarging the perforation, 7 septal rotation flaps, 1,12,13 inferior turbinate pedicle flaps, 8 sublabial mucosal flaps, flaps, 16 tissue expansion, 17 and facial artery musculomucosal flaps. 18 Several autologous interposition grafts, including temporal muscle fascia, 1 septal cartilage, 19 nasal turbinate, 20 conchal cartilage, 21 mastoid bone with periosteum, 22 ear tragus cartilage with perichondrium, 23 perichondrocutaneous, 14 pericranium, 6 ethmoid bone, 6 and iliac crest, 19 as well as an acellular human dermal allograft, have also been used for SP repair. 13 Joseph, in 1931, and Safian, in 1935, brought into practice the technique proposed by Steifet in 1926, which was based on the transposition of an inferior turbinate flap.…”
Section: Commentmentioning
confidence: 99%
“…It has been used successfully for reconstruction of various defects in nasal lining. 9,19,20 Unilateral or bilateral, superiorly based facial artery musculomucosal flaps provide moist mucosal lining based on an axial blood supply. This blood supply is quite robust, making it possible to raise very long flaps that can be folded for additional versatility.…”
Section: Mucosal Flaps: Intraoralmentioning
confidence: 99%